Pengaruh Pakan Berbasis Silase dengan Penambahan Minyak Sawit dan Minyak Kelapa terhadap Kecernaan pada Domba Betina: The Effect of Silage-Based Feed with Added Palm Oil and Coconut Oil on Digestibility in Ewes - Anggun Cantika, Neng Risviana; Diapatri, Didid Diapari; Manu Hara Karti , Panca Dewi (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
This study aimed to measure the level of nutrient digestibility in local sheep fed high-energy silage-based feed with added palm oil and coconut oil. Twelve adult ewes thathad given birth with an average body weight of 26.12 ± 3.13 kg and an average initial body condition score (BCS) of 1.7 ± 0.57 were used in this experiment. The basalt ration used was silage complete ration Sorinfer consisting of sorghum, indigofera, and concentrate. The treatments were P0= Sorinfer + 6% soybean meal (control), P1= P0 + 3% palm oil, and P2= P0 + 3% coconut oil. The variables measured included the consumption and digestibility of dry matter and nutrients. The data obtained were analyzed using ANOVA. If the results showed significant differences, further tests were performed using the Duncan test. The results showed that the addition of vegetable oil to the ration was able to increase the consumption of crude fat but decrease its digestibility. The addition of 3% coconut oil (P2) effectively increased the digestibility of organic matter, crude protein, and digestibility of Nitrogen-Free Extract (NFE) compared to controls, while rations with the addition of 3% palm oil (P1) effectively increased the digestibility of crude fiber compared to controls. The digestibility of ration nutrients in the 3% coconut oil addition treatment (P2) was more optimal than the control treatment and the addition of palm oil (P1). Key words: local ewes, nutrient consumption, nutrient digestibility, oil, silage